Identifikasi dan Karakterisasi Sumber Daya Genetik Buah-buahan di Kabupaten Buleleng - I GUSTI AGUNG BAGUS SURADARMA; GEDE WIJANA; I NYOMAN SUTEDJA (Agrotrop : Journal on Agriculture Science, 2018)
Identification and Characterization of Fruit Genetic Resources in Buleleng Regency. Fruits have great potential to be developed both to meet the needs of domestic and foreign demand, because the fruits is a source of supply of vitamins, minerals, and fiber needed in the daily menu. Several types of fruit are also required as spa, medicines, and as a means of upakara. One of the prospective development of fruits in Bali is Buleleng. Types of fruit in Buleleng are grape, mango, durian, rambutan and banana. Until now there has been generally identified genetic resources fruits in Buleleng. This study aims to identify, profile and draw up a map of the geographic distribution of genetic resources of fruits in Buleleng. Implementation of the study consists of four activities, namely: secondary data collection, survey of the types of genetic resources and distribution, identification of morphological and agronomic characters of each type of genetic resources and the growing environment and the benefits of fruits. The seeded fruit is determined by Location Quotion (LQ). Based on the observations in the field, Buleleng has a wide range of genetic resources. In a direct observation to the field there are 32 kinds of fruit and 31 sub-types of fruit. Fruits are grouped based on the economic value and their role, including: commercial fruit, rare fruit, fruit for upakara and fruit for medicine. Based on the calculation of LQ method, Buleleng has four featured i.e. avocado, grape, mango and rambutan (LQ>1).